Perspectives of Belarus in the Eurasian Economic Community customs union - Veka, Aliaksei; Müller, David, 1979-; Sudliankou, Aliaksandr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
The thesis will focus on impacts of the Eurasian Economic Community customs union on Belarus. The initial part of the research will define reasons and conditions for creation of the Customs Union, describe stages and context of its development and and current state of integration. The text will then focus on practical issues of the Customs Union and its operations, including the potential benefits and drawbacks. Part of the study will be also dedicated to political aspects of members' participation in the integration. Finally, the thesis will analyze possible measures to improve functioning of the Customs Union and perspectives for Belarus with regard to its participation in the union.
Vedoucí práce: David Müller
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: cestovní ruch [obor dipl. práce]; diplomové práce; master's theses